PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI PADA MATERI SISTEM KOORDINASI KELAS XI SMA - Dina Aprilla Zefira; Mariani Natalina. L; Arnentis Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the quality of the animated video learning media on the material of the XI high school class coordination system developed. This research is a Research and Development (R&D) with analyze, design, development, implementation and evaluation stages. This research was only carried out until stage 3, namely development. The analysis, design, development of internal validation and phase I limited trials were carried out at the Biology Education Faculty of the University of Riau. Meanwhile, for external validation and limited trial phase II, it was conducted at SMAN 1 Pekanbaru. The research was conducted in January-June 2022. There are two data collection instruments used: validation sheets and respondent questionnaires. The results of the validation of animated videos on the coordination system material for class XI SMA are at an average value of 3.81 with a very valid category. The result of the limited trial score I was 3.79 with a very good category. The result of the limited trial score II was 3.90 in the very good category. Thus, the animation video on the coordination system material for class XI SMA has been successfully developed with very good quality and can be implemented on a wider scale.Key Words: Learning Media, Video Animation, Coordination System